The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1556264620904272
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Defaults and Consent for Participation in a Learning Health Care System: An Empirical Study

Abstract: We report a preregistered study that was designed to answer three questions about using transparent defaults to increase participation in a hypothetical learning health care system. Do default options influence consent to participate in learning activities within a learning health care system? Does transparency about default options decrease the effect of the defaults? Do people reconsider their choice of participation once they are informed about the defaults applied? In our study, application of the defaults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…For 10 (13.2%) of 76 studies, ethics, policy, or governance was the primary focus. These studies examined LHS ethics, policy, and governance issues through qualitative interviews (n=3, 30%) [ 60 - 62 ] or focus groups (n=3, 30%) [ 63 - 65 ], quantitative methods (n=3, 30%) [ 66 - 68 ], or mixed-method designs (n=1, 10%) [ 69 ]. Participants in these studies included health care consumers [ 63 , 66 - 69 ], ethical review board members [ 61 , 64 ], institutional leaders [ 62 ], health care providers, managers, and researchers [ 60 , 61 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For 10 (13.2%) of 76 studies, ethics, policy, or governance was the primary focus. These studies examined LHS ethics, policy, and governance issues through qualitative interviews (n=3, 30%) [ 60 - 62 ] or focus groups (n=3, 30%) [ 63 - 65 ], quantitative methods (n=3, 30%) [ 66 - 68 ], or mixed-method designs (n=1, 10%) [ 69 ]. Participants in these studies included health care consumers [ 63 , 66 - 69 ], ethical review board members [ 61 , 64 ], institutional leaders [ 62 ], health care providers, managers, and researchers [ 60 , 61 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The implications of sharing data were a central concern in all 10 studies. Specific concerns regarding health data sharing included the patients’ right to consent to, and to be notified of, data sharing [ 66 ], patient privacy [ 63 ], and profit-driven data custodianship [ 69 ]. Studies found statistically significant factors influencing health consumers’ positive attitudes toward data sharing, including higher education, low concerns regarding privacy [ 67 , 68 ], and the belief that participation in research is an ethical imperative [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies do not apply a transparent nudge, the topic has grown more salient in recent studies. In total, four studies have tested how transparent defaults change the effectiveness of the previously tested non-transparent defaults (Goswami & Urminsky, 2016;Bruns et al, 2018;Paunov et al, 2019;Dranseika & Piasecki, 2020). Researchers that apply transparent defaults seem aware of how they change the choice situation.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…The framing adds salience to the default option and can imply a social norm, particularly if the target behavior is not conflicting with previously learned moral mandates and is not perceived to serve the self-interests of the choice architect (Paunov et al 2019). The majority of studies report similar nudge success for transparent defaults compared to non-transparent ones (Goswami & Urminsky, 2016;Bruns et al, 2018;Dranseika & Piasecki, 2020). At this stage, we agree with the observation by Loewenstein et al (2015) that transparent nudges do not work less when individuals are explicitly informed that a default rule is in place.…”
Section: Empirical Findingsmentioning
confidence: 99%